Transformational Leadership in The Era of Society 5.0: A Conceptual Review - Munawwaroh, Tafiek (PT Hakhara Akademia Indonesia, 2024)
This research aims to analyze transformational leadership in the era of society 5.0. The research method used in this research is the library method. The findings from this research are that transformational leadership in the era of society 5.0 is leadership that means changing the followers or subordinates being led towards organizational development. This is because in the era of society 5.0 which prioritizes humans as the source or center of innovation while remaining technology-based so that this leadership model is able to bring change towards the era of society 5.0.